The relationship between alternative population and migration series - a comment - Hughes, JG (Economic & Social Studies, 1981)
In their recent paper on the derivation of annual population estimates Whelan and Keogh (1980) implicitly assume that the number on the Electoral Register refers to Apri l 15 ? the date on which the Register comes into effect each year. However, since the qualifying date for inclusion on the Register is September 15, the Electoral Register figures should be adjusted to reflect the number expected on the Register on Apri l 1 each year. This can be done by linear interpolation of the September figures and the resulting estimates can be used to derive annual population estimates using Whelan and Keogh's ratio formula. The original and adjusted Electoral Register figures and the population and net migration estimates which are derived from the adjusted figures are shown in Table 1 together with the difference between the CSO's post-censal population estimates, the adjusted population estimates, Whelan and Keogh's ratio estimates of the population and the CSO's pre-censal population estimates.
Keywords: Economics; Sociology